Xq22 deletions and correlation with distinct neurological disease traits in females: Further evidence for a contiguous gene syndrome. - Hijazi, Hadia; Coelho, Fernanda S; Gonzaga-Jauregui, Claudia; Bernardini, Laura; Mar, Soe S; Manning, Melanie A; Hanson-Kahn, Andrea; Naidu, Sakkubai; Srivastava, Siddharth; Lee, Jennifer A; Jones, Julie R; Friez, Michael J; et al. (Hum Mutat, 2020)
Xq22 deletions that encompass PLP1 (Xq22-PLP1-DEL) are notable for variable expressivity of neurological disease traits in females ranging from a mild late-onset form of spastic paraplegia type 2 (MIM# 312920), sometimes associated with skewed X-inactivation, to an early-onset neurological disease trait (EONDT) of severe developmental delay, intellectual disability, and behavioral abnormalities. Size and gene content of Xq22-PLP1-DEL vary and were proposed as potential molecular etiologies underlying variable expressivity in carrier females where two smallest regions of overlap (SROs) were suggested to influence disease. We ascertained a cohort of eight unrelated patients harboring Xq22-PLP1-DEL and performed high-density array comparative genomic hybridization and breakpoint-junction sequencing. Molecular characterization of Xq22-PLP1-DEL from 17 cases (eight herein and nine published) revealed an overrepresentation of breakpoints that reside within repeats (11/17, ~65%) and the clustering of ~47% of proximal breakpoints in a genomic instability hotspot with characteristic non-B DNA density. These findings implicate a potential role for genomic architecture in stimulating the formation of Xq22-PLP1-DEL. The correlation of Xq22-PLP1-DEL gene content with neurological disease trait in female cases enabled refinement of the associated SROs to a single genomic interval containing six genes. Our data support the hypothesis that genes contiguous to PLP1 contribute to EONDT.
Keywords: Child; Child, Preschool; Chromosome Breakpoints; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, X; Comparative Genomic Hybridization; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Nervous System Diseases; Pedigree; Phenotype; Quantitative Trait, Heritable; Repetitive Sequences, Nucleic Acid; Sex Factors; Syndrome; X Chromosome Inactivation

A comprehensive clinical and genetic study in 127 patients with ID in Kinshasa, DR Congo. - Lumaka, Aimé; Race, Valerie; Peeters, Hilde; Corveleyn, Anniek; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Song, Xiaofei; Mubungu, Gerrye; Posey, Jennifer; Lupski, James R; Vermeesch, Joris R; Lukusa, Prosper; et al. (Am J Med Genet A, 2018)
Pathogenic variants account for 4 to 41% of patients with intellectual disability (ID) or developmental delay (DD). In Sub-Saharan Africa, the prevalence of ID is thought to be higher, but data in Central Africa are limited to some case reports. In addition, clinical descriptions of some syndromes are not available for this population. This study aimed at providing an estimate for the fraction of ID/DD for which an underlying etiological genetic cause may be elucidated and provide insights into their clinical presentation in special institutions in a Central African country. A total of 127 patients (33 females and 94 males, mean age 10.03 ± 4.68 years), were recruited from six institutions across Kinshasa. A clinical diagnosis was achieved in 44 but molecular confirmation was achieved in 21 of the 22 patients with expected genetic defect (95% clinical sensitivity). Identified diseases included Down syndrome (15%), submicroscopic copy number variants (9%), aminoacylase deficiency (0.8%), Partington syndrome in one patient (0.8%) and his similarly affected brother, X-linked syndromic Mental Retardation type 33 (0.8%), and two conditions without clear underlying molecular genetic etiologies (Oculo-Auriculo-Vertebral and Amniotic Bands Sequence). We have shown that genetic etiologies, similar to those reported in Caucasian subjects, are a common etiologic cause of ID in African patients from Africa. We have confirmed the diagnostic utility of clinical characterization prior to genetic testing. Finally, our clinical descriptions provide insights into the presentation of these genetic diseases in African patients.
Keywords: Adolescent; Adult; Algorithms; Child; Child, Preschool; Comparative Genomic Hybridization; Democratic Republic of the Congo; Developmental Disabilities; Disease Management; Exome Sequencing; Facies; Female; Genetic Association Studies; Genetic Markers; Genetic Predisposition to Disease; Genetic Testing; Homeodomain Proteins; Humans; Infant; Intellectual Disability; Male; Phenotype; Syndrome; Transcription Factors; Trinucleotide Repeat Expansion; Trinucleotide Repeats; Workflow; X Chromosome Inactivation; Young Adult

Identification of Intellectual Disability Genes in Female Patients with a Skewed X-Inactivation Pattern. - Fieremans, Nathalie; Van Esch, Hilde; Holvoet, Maureen; Van Goethem, Gert; Devriendt, Koenraad; Rosello, Monica; Mayo, Sonia; Martinez, Francisco; Jhangiani, Shalini; Donna M Muzny; Richard A Gibbs; Lupski, James R; et al. (Hum Mutat, 2016)
Intellectual disability (ID) is a heterogeneous disorder with an unknown molecular etiology in many cases. Previously, X-linked ID (XLID) studies focused on males because of the hemizygous state of their X chromosome. Carrier females are generally unaffected because of the presence of a second normal allele, or inactivation of the mutant X chromosome in most of their cells (skewing). However, in female ID patients, we hypothesized that the presence of skewing of X-inactivation would be an indicator for an X chromosomal ID cause. We analyzed the X-inactivation patterns of 288 females with ID, and found that 22 (7.6%) had extreme skewing (>90%), which is significantly higher than observed in the general population (3.6%; P = 0.029). Whole-exome sequencing of 19 females with extreme skewing revealed causal variants in six females in the XLID genes DDX3X, NHS, WDR45, MECP2, and SMC1A. Interestingly, variants in genes escaping X-inactivation presumably cause both XLID and skewing of X-inactivation in three of these patients. Moreover, variants likely accounting for skewing only were detected in MED12, HDAC8, and TAF9B. All tested candidate causative variants were de novo events. Hence, extreme skewing is a good indicator for the presence of X-linked variants in female patients.
Keywords: Carrier Proteins; Cell Cycle Proteins; Chromosomal Proteins, Non-Histone; DEAD-box RNA Helicases; Exome; Female; Genetic Variation; Humans; Intellectual Disability; Membrane Proteins; Methyl-CpG-Binding Protein 2; Nuclear Proteins; Sequence Analysis, DNA; X Chromosome Inactivation

Two male sibs with severe micrognathia and a missense variant in MED12. - Prescott, Trine E; Kulseth, Mari Ann; Heimdal, Ketil R; Stadheim, Barbro; Hopp, Einar; Gambin, Tomasz; Coban Akdemir, Zeynep H; Jhangiani, Shalini N; Donna M Muzny; Richard A Gibbs; Lupski, James R; Stray-Pedersen, Asbjørg (Eur J Med Genet, 2016)
Missense variants in MED12 cause three partially overlapping dysmorphic X-linked intellectual disability (XLID) syndromes: Lujan-Fryns syndrome (also known as Lujan syndrome), FG syndrome (also known as Opitz-Kaveggia syndrome) and X-linked Ohdo syndrome. We report a family with two severely micrognathic male sibs, a 10½ year old boy and a fetus, in which hemizygosity for a previously unreported missense variant in exon 13 of MED12 (NM_005120.2), c.1862G > A, p.(Arg621Gln) was detected by whole exome sequencing. The affected sibs shared no other rare variant with relevance to the phenotype. X-chromosome inactivation in blood was completely skewed (100:0) in the unaffected heterozygous mother, most likely as a result of preferential inactivation of the X-chromosome harbouring the missense variant in MED12. Neither the unaffected brother nor the unaffected maternal grandfather carried the missense variant in MED12. In the 10½ year old boy, upper airway obstruction secondary to Pierre Robin sequence necessitated a tracheostomy for the first 10 months of life. He has mild to moderate intellectual disability and some dysmorphic features seen in MED12-related syndromes. In addition, he has a horizontal gaze paresis, anomalies of the inner ear, and a cervical block vertebra. This report contributes to the expanding phenotypic range associated with MED12-mutations.
Keywords: Exons; Genes, X-Linked; Genetic Association Studies; Genotype; Humans; Infant; Male; Mediator Complex; Micrognathism; Mutation, Missense; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Severity of Illness Index; Siblings; Tomography, X-Ray Computed; X Chromosome Inactivation